LED light stress induced biomass and fatty acid production in microalgal biosystem, Acutodesmus obliquus - Choi, Yong-Keun; Kumaran, Rangarajulu Senthil; Jeon, Hyeon Jin; Song, Hak-Jin; Yang, Yung-Hun; Lee, Sang Hyun; Song, Kyung-Guen; Kim, Kwang Jin; Singh, Vijay; Kim, Hyung Joo (Pergamon Press Ltd., 2015)
Microbial algal system can serve as a potential source for the production of much high value bioproducts and biofuels. The quality and intensity of light are the key elements to optimize the production of algal biomass and fatty acid contents. This study presents the effect of differential LED flashing light conditions on the growth of microalgae, Acutodesmus obliquus. The induced light stress was optimized for its bio, mass and fatty acid content. The microalgae are exposed to various frequency of intermittent LED flashing light (blue and red lights) at three different phases in the 18 day cell growth (log, lag and stationary phase). The frequency of light flashing rate was adjusted to 120, 10, 5, 3.75, and 1 times per min. The effect of light stress on growth and fatty acids composition of A. abliquus induced an increase in algae growth and fatty acid production. Different optimal timing for light stress was subjected to elucidate the effect of light stress on algae growth and fatty acid production. The results showed an increase in the algae growth (1.2 mg/L of chl a content) under light stress condition at FT10 (flashing time, 10 times per min) from the initial day (log phase) compared with the control experiment (0.4 mg/L of chl a content). However, the total fatty acids (71 mg/g) and volumetric FAME production (9.4 ml/l) level was found to be significant under FT5 (flashing time, 5 times per min), adopting flashing light from day 10 (stationary phase). TEM studies also revealed the deposition of lipid to be largest in the 18 day old cells under flashing light (FT5) condition, representing maximum accumulation of lipids bodies (up to 770 nm diameter in particle size) occupying approximately 42% of the total area of the cell. (C) 2015 Elsevier B.V. All rights reserved.